2021
DOI: 10.1093/bjsw/bcaa240
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Lived Experience of Social Work Students in Their Field Training during the Coronavirus Crisis: Insights from Photovoice-Based Research

Abstract: The present paper is based on a photovoice study conducted with sixteen undergraduate social work students in their third year of study, examining their real-time lived experience of their fieldwork training in the immediate aftermath of the outbreak of the coronavirus pandemic. The findings of the study, based on an analysis of sixty-six photovoices, indicate four main narratives encapsulating the students’ real-time lived experiences: (i) the challenges of encountering the crisis; (ii) conceptualizing the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 39 publications
0
3
0
5
Order By: Relevance
“…2020; Batič 2021;Dempsey idr. 2022;Jefferies, Davis in Mason 2021;Kim 2020;Kidd in Murray 2020;Kodele, Kustec in Rape Žiberna 2021;Malka 2022;McFadden idr. 2020;Morris idr.…”
Section: Obravnava Vsebine Alternativa In Prilagoditev Praktičnega Us...mentioning
confidence: 99%
See 2 more Smart Citations
“…2020; Batič 2021;Dempsey idr. 2022;Jefferies, Davis in Mason 2021;Kim 2020;Kidd in Murray 2020;Kodele, Kustec in Rape Žiberna 2021;Malka 2022;McFadden idr. 2020;Morris idr.…”
Section: Obravnava Vsebine Alternativa In Prilagoditev Praktičnega Us...mentioning
confidence: 99%
“…Izkustveno učenje skozi podporo za skupnost je bilo v našem primeru umeščeno v kontekst aktualnega, nepoznanega in negotovega učnega okolja. Študentovo praktično pedagoško usposabljanje je bilo umeščeno v zahtevno, vsem deležnikom neznano situacijo, s katero se je študent moral neposredno soočiti (Malka 2022;Morris idr. 2020).…”
Section: Izkustveno Učenje Za Strokovne Odzive Na Aktualne Potrebe In...unclassified
See 1 more Smart Citation
“…2020;Batič 2021;Dempsey idr. 2022;Jefferies, Davis in Mason 2021;Kim 2020;Kidd in Murray 2020;Kodele, Kustec in Rape Žiberna 2021;Malka 2022;McFadden idr. 2020;Morris idr.…”
Section: Obravnava Vsebine Alternativa In Prilagoditev Praktičnega Us...mentioning
confidence: 99%
“…Researchers required methods that would allow "direct" access and document meaningful life experiences, perspectives, and priorities (Santana et al, 2021). Some authors (Malka, 2021a(Malka, , 2021bSy et al, 2020) suggested photovoice for remote data collection. Photovoice is participatory action research that combines participants' photographs and voices (Rodrigues et al, 2008;Wang & Burris, 1997) to document life experiences, needs, difficulties, and desires in photographs that are discussed in critical reflection.…”
Section: Introductionmentioning
confidence: 99%